PENGARUH PERSEPSI PERILAKU KEPEMIMPINAN, MOTIVASI KERJA, DAN PENGEMBANGAN PROFESIONALISME GURU TERHADAP KINERJA GURU SEKOLAH LANJUTAN ATAS DI YAYASAN AL-ASY’ARIYYAH KALIBEBER WONOSOBO (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
This study aims at determining the influence of: (1) the leadership behavior perception, teachers’ work motivation and teachers’ professional development toward the teachers’ performance (2) the leadership behavior perception partially againsts teachers’ performance (3) the teachers’ work motivation against the teachers’ performance (4 ) teachers’ professional development againsts the teachers’ performance.This research was conducted in the high schools belong to Al-Asy’ariyyah Foundation, Kalibeber, Wonosobo. This research was a quantitative study using survey method. SMA Takhassus Al-Qur’an Wonosobo, The subjects of this research are 95 teachers of  SMK Takhassus Al-Qur’an Wonosobo and MA Takhassus Qur’an Wonosobo . This research used employed experiment because it is a population research. The data collection technique used in this study was questionnaire. The data analysis technique used in this study was multiple regressions with three predictors. The integrated hypothesis testing conducted by using F-test followed by t-test. The data analysis was conducted by using SPSS v.16. The total effective contribution was gained from  the result of determination coefficient value multiple by the Standardized Beta Coefficient  with Zero-order Correlations value multiplied by 100% for each independent variable.The results of the data analysis show that:  (1) The leadership behavior perception, teachers’ work motivation and teachers’ profesional development simultaneously give  significantly positive influence to the teachers’ performance by 58,57%, (2) The perceptions of leadership behavior give unsignificantly positive  influence to the teachers’ performance with the effectiveness contribution at 6,01%, (3) The work motivations give  unsignificantly positive influence to the  teachers’ performance with the effectiveness contribution at 12,61%, (4) The teachers’ professional development give very significant positive influence to the teachers’ performance with the effectiveness contribution at 39,95%.